A 3-year investigation into the incidence and nature of cricket injuries in elite South African schoolboy cricketers - Trella, C (South African Journal of Sports Medicine, 2012)
Objectives. Injury surveillance is fundamental to preventing and reducing the risk of injury. The aim of this study is to determine the incidence of the injuries sustained by elite schoolboy cricketers over three seasons (2007 - 2008, 2008 - 2009, 2009 -2010) to identify possible risk factors. Methods. Sixteen provincial age-group cricket teams (Under 15, Under 17 and Under 18) competing in national age-group tournaments were asked to complete questionnaires to obtain the following information for each injury: (i) anatomical site; (ii) month; (iii) cause; (iv) whether it was a recurrence of a previous injury; (v) whether the injury had reoccurred again during the season; and (vi) biographical data. Injuries were grouped according to the anatomical region injured. All players were requested to respond, irrespective of whether an injury had been sustained. The Sample Statistical Analysis System (SAS) was used to compute univariate statistics and frequency distributions. Of the 1 292 respondents 366 (28%) sustained a total of 425 injuries. The U15 and U17 groups sustained 166 (39%) and 148 (35%) injuries, respectively, more than the 111 injuries sustained by the U18 group (26%). These injuries were predominantly to the lower (46%) and upper (35%) limbs and occurred primarily during 1-day matches (31%), practices (27%) and with gradual onset (21%). The primary mechanism of injury was bowling (45%) and fielding, including running to field the ball (33%). Forty-two lumbar muscle strains, 18 hamstring strains, 17 spondylolisthesis and 17 ankle sprains occurred. The injuries were acute (50%), chronic (42%) and acute-on-chronic (8%), with 24% and 46% being recurrent injuries from the previous and current seasons, respectively. Results. Similar injury patterns occurred in studies of adult cricketers, with slight differences in the nature and incidence of injuries found for the various age groups. The U15 group sustained less serious injuries which resulted in them not being able to play for between 1 - 7 days (54%), with more injuries occurring in the pre-season period (28%) than the other groups. The U17 group sustained the most lumbar muscle strains (n=23), while the U18 group sustained more serious injuries with 60% of the injuries resulting in them not being able to play for 8 or more days. Conclusion. Young fast-bowlers of all ages remain at the greatest risk of injury while slight differences in the nature and incidence of injuries occurred in the different age groups. It is recommended that cricket administrators and coaches need to implement an educational process of injury prevention and management.